Alternative conservation methodologies: valorization and reuse of built heritage. Case study Exhacienda San Diego del Jaral, Mexico - González-Franco Herrera, Angélica; Muñoz Nájera, Ricardo (Ge-conservacion, 2017)
Architectural conservation had its origins on the “monumental” perspective, founded on the restoration as the methodological approach. Although there are different conservation strategies, it is important to consider new proposals. The reuse of the built preexistences based on management plans, presents itself as an integrated strategy; where conservation, social welfare, environmental and economical sustainability converge by giving relevance to the existing architecture, located in the different urban environments regardless if it is a “monumental” or a minor architecture. The case study of the Exhacienda San Diego del Jaral is an example of the current conservation problem in Mexico: a vast amount of built heritage that due to the lack of human and financial resources is abandoned. They are not inserted in a comprehensive conservation strategy, where it should overcome the paradigm of the vision of the heritage as public expenditures and move it, to a useful model for economic development.